The association between motivation and fruit and vegetable intake: The moderating role of social support. (1st January 2016) - McSpadden, Kate E.; Patrick, Heather; Oh, April Y.; Yaroch, Amy L.; Dwyer, Laura A.; Nebeling, Linda C.
Abstract: Despite knowing that fruit and vegetable (FV) intake promotes health and well-being, few U.S. adults meet current guidelines. Thus, understanding people's motivation for FV intake is important for predicting dietary behavior. Applying self-determination theory, the goal of this study was to examine the role of social support as a potential moderator of the link between autonomous and controlled motivations and FV intake. Cross-sectional data from 2959 adults in the United States were analyzed. Autonomous motivation and perceived social support were positively associated with FV intake, while controlled motivation was negatively associated with FV intake. Additionally, there was evidence that the negative association between controlled motivation and FV intake was attenuated by higher levels of perceived social support. Findings suggest the need for a more comprehensive approach to understanding the role of motivation in health behaviors like FV intake and the potential roles played by friends and family in these motivational processes. Highlights: Self-determination theory emphasizes the role of motivation for health behaviors. Motivation and social support were associated with fruit and vegetable intake (FV). Social support attenuated the association between controlled motivation and FV. Findings suggest a role of social support for health motivations and behaviors.